Kesiapan Siswa dalam MenyelesaikanTugas Sekolah - Endriani, Ninil; Syukur, Yarmis (Konselor, 2015)
School task in the form of school homework assignment (PR) is intended to provide insight into the subject matter to students who must the finishing. The fact is there are still students who didn't make the task because not understand the task, do not have book sources, there are students who cheat task friend and late to collect it. This phenomena indicate is readiness of students completing school task still less . The purpose of this research described readiness in school student finished the taskseen from: (1) understanding students with task (2) preparation of source material/task (3) completion of Task (4) collect the task. The results showed that students have the readiness in completing the task of schools, however there are still some students don't have the readiness.